Seroprevalence of brucellosis in camels and humans in the Al-Qassim region of Saudi Arabia and its implications for public health - Abdulaziz M. Almuzaini; Abdullah S. M. Aljohani; Ahmed I. Alajaji; Ayman Elbehiry; Adil Abalkhail; Abdulrahman Almujaidel; Sahar N. Aljarallah; Hazem R. Sherif; Eman Marzouk; Abdelmaged A. Draz (AMB Express)
Abstract Brucellosis is a significant zoonotic disease caused by intracellular, gram-negative bacteria from the genus Brucella. Although camels are classified as secondary hosts for Brucella species, they are among the most susceptible and vulnerable animals to brucellosis, particularly Brucella abortus (B. abortus) and Brucella melitensis (B. melitensis). The present study aimed to investigate the epidemiology of camel brucellosis as a zoonotic disease by determining the seroprevalence of brucellosis in both camels and humans, assessing potential risk factors (e.g., age, size, and location), and conducting molecular characterization of Brucella spp. associated with abortion in camels. The Rose Bengal Test (RBT), Antigen Rapid Brucella Antibody Test (ARBT), indirect enzyme-linked immunosorbent assay (I-ELISA), and complement fixation test (CFT) were used to detect brucellosis in both camels and humans. Additionally, a molecular method using polymerase chain reaction was used as a confirmatory technique. A total of 625 camel serum samples and 100 human serum samples were collected in sterile vacuum tubes from various camel farms and individuals across different localities in the Al Qassim region. Additionally, samples from 10 confirmed Brucella-infected camels (including the uterus and supramammary lymph nodes) were analyzed. The results indicated that the overall prevalence of brucellosis in camel sera was 9.72%, as determined by RBT, and 8.16%, as determined by ARBT. In contrast, the overall prevalence of brucellosis in human sera from febrile patients was found to be 17% via RBT. Notably, 57.98% of camel sera that tested positive for Brucella antibodies via RBT were also positive according to I-ELISA and CFT. Furthermore, 42.1%, 70.58%, and 47.05% of human sera that were positive for Brucella antibodies as determined by RBT were also positive according to I-ELISA and CFT, respectively. The highest seropositivity for camel brucellosis was observed in female camels, particularly in the Unaizah area of the Qassim region and among the Homr breed. The prevalence of human brucellosis was highest among females and individuals who consumed raw milk. At the molecular level, B. melitensis biovar 3 was detected in the examined tissues. In conclusion, intervention measures are vital for reducing brucellosis in humans and camels. Public awareness campaigns should highlight the importance of protective clothing when handling aborted she-camels and the need to boil or pasteurize milk. Additionally, studies should differentiate between vaccinated and nonvaccinated camels, and standardizing serological tests for diagnosing brucellosis should be prioritized.